Tax Goes to Campus as an Effort to Include Tax Awareness at LP3I Tasikmalaya Polytechnic - Usmar, Andi; Sofyan, Harnavela; Surayuda, Rama Nugraha Irawan; Munggaran, Rangga; Sofyan, Verra Rosyalia Widia; Fitriani, Rani Ligar; Sanjayyana, Adzka Rosa; Bahiyyah, Khariidatul; Kurniawati, Yuyun; Romdoni, Nijar Kurnia; Sutarsa, Monika (Journal of Community Service and Society Empowerment, 2025)
This activity explores the implementation of the "Tax Goes to Campus" program as an inclusive effort to raise tax awareness among students at Politeknik LP3I Tasikmalaya. Held on October 31, 2024, the program aimed to enhance understanding and awareness of tax obligations among the younger generation in alignment with the vision of a Golden Indonesia 2045. Through a participatory approach, this community service involved tax education delivered by experts from the Tasikmalaya Tax Office. The methods used included interactive seminars, discussions, and post-session evaluations to assess the effectiveness of this initiative. Results indicated a significant increase in students' understanding of tax contributions to national development and their roles as responsible citizens. This activity concludes that such programs promote tax literacy and contribute to long-term national growth. This activity implies that sustainable tax education in higher education is essential to shape future leaders who are proactive and tax-aware.